Income Taxes, Property Values, and Migration - Amihai Glazer; Vesa Kanniainen; Panu Poutvaara (Center for Economic Studies and ifo Institute (CESifo), 2003)
We consider taxation by a Leviathan government and by a utilitarian government in the presence of heterogeneous locations within a country, when migration from one country to another is and is not possible. In a closed economy, a utilitarian government may transfer income from the poor to the rich to reduce rents earned by absentee landlords. When the rich are mobile, a tax on them induces little migration because the tax will reduce the rents on land inhabited by the rich. A race to the bottom need not appear.
Keywords: H21; H70; R21; R23; 330; taxes; land rents; property values; migration; redistribution